(untitled) (Eurasian Research Bulletin, 2023)
One of the most important problems in front of our country is currently ensuring security. Therefore, the first lesson in all educational institutions is the Independence and Peace lesson. Understanding the urgency of the problem is formed on the national and state levels. This article discusses the current state of life safety culture.